Technique, experience and invention in ballroom dancing (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The following article discusses ballroom dance as a space for invention and learning. Ballroom dances are understood as a social field that is organized around the interest in this specific dance technique. To conceptualize this, we draw from the writings of Tonial (2011) and Dickow (2020), who research ballroom dance. The notion of technique is delineated through Mauss (2003) and Ortega y Gasset (1963), in addition to the writings of Taylor (2013) and Schechner (2003) regarding performance, allowing us to view ballroom dances as a learning system and as a social context and practice that can be defined by its social significance and history.
Keywords: ballroom dance; experience; dance event; technique; performance